Associations of early life stress with leptin and ghrelin in healthy young adults. (March 2023) - Daniels, Teresa E.; Mathis, Karen Jennings; Gobin, Asi Polly; Lewis-de los Angeles, William W.; Smith, Eric M.; Chanthrakumar, Pranavan; de la Monte, Suzanne; Tyrka, Audrey R.
Abstract: Background: Childhood adversity is a major risk factor for cardiometabolic health problems. Stress-related changes in diet suggest a role for endocrine factors that influence dietary intake, such as leptin and ghrelin. These hormones influence metabolism and may contribute to the relationship of early adversity, mental, and cardiometabolic health. This study examined levels of leptin and ghrelin in a sample of young adults with and without early life stress (ELS). Methods: Young adults ages 18–40 ( N = 200; 68.5% female) were recruited from the community. Participants with ELS ( N = 118) had childhood maltreatment, and a subset, n = 92 (78.0%) also had parental loss, and n = 65 (55.1%) also had a current psychiatric disorder. Control participants ( N = 82) had no maltreatment, parental loss, or psychiatric disorders. Standardized interviews and self-reports assessed demographics, adversity, medical/psychiatric history, and health behaviors. Exclusion criteria included medical conditions and current medications other than hormonal contraceptives. Body Mass Index (BMI) and other anthropometrics were measured, and fasting plasma was assayed for total ghrelin and leptin with the Bio-Plex Pro Human Diabetes Panel. Results: While ELS was significantly associated with greater leptin ( r = .16, p = .025), a finding which held when adjusted for age and sex ( F (3196)= 28.32, p = .011), this relationship was abolished when accounting for BMI ( p = .44). Participants with ELS also had significantly lower total ghrelin ( r = .21, p = .004), which held adjusting for age and sex ( p = .002) and was attenuated ( p = .045) when the model included BMI ( F =46.82, p < .001). Current psychiatric disorder was also a significant predictor of greater leptin ( r = .28, p < .001) and lower ghrelin ( r = .29, p = .003). In the model with ELS and covariates, psychiatric disorder remained significant ( F =7.26, p = .008) and ELS was no longer significant ( p = .87). Associations with severity and recent perceived stress were also examined. Conclusion: The relationship of ELS and leptin was no longer significant when accounting for BMI, suggesting potential avenues for intervention. Ghrelin findings persisted after correction for BMI, which may be secondary to physiological differences in the regulation of these hormones (leptin is produced by adipocytes, whereas ghrelin is produced primarily in the GI tract). Lastly, these findings suggest that psychiatric functioning may be a key component contributing to the relationship of lower total ghrelin and childhood adversity. Highlights: ● Among healthy young adults, those with early life stress (ELS) have greater levels of leptin and lower levels of ghrelin. ● The association of ELS and leptin remained significant after controlling for age and sex but was abolished when body mass index (BMI) was included in the model. ● The significant association of ELS with lower ghrelin withstood correction for age, sex, and BMI. ● Psychiatric disorder was also a significant predictor of ghrelin controlling for age, sex, and BMI.